Virus-induced asthma exacerbations in Vietnamese preschoolers - Nguyen Thuy Van Thao; Tran Anh Tuan; Pham Hung Van; Le Thuong Vu (Italian Journal of Medicine)
The health burden of asthma is mainly related to asthma exacerbation, whose most common trigger is viral infection. Additionally, preschool children experience the highest rate of morbidity from asthma. The objective of this cross-sectional study was to find out the prevalence of virus-induced asthma exacerbations among hospitalized preschoolers in the south of Vietnam with tropical weather. A total of 133 children aged 3-5 years admitted to the Children’s Hospital 1 with asthma exacerbations were enrolled. Within 24 hours of admission, nasopharyngeal swabs were tested for popular respiratory viruses by multiplex real-time polymerase chain reaction, and the genotype of human rhinovirus (HRV) was subsequently determined by Sanger sequences. Virus infections accounted for 48.9% of hospitalized preschoolers with moderate or severe asthma exacerbations. HRV was the most common pathogen (55.4%), with more than half of the cases being HRV-C (58.3%). The group of HRV-induced asthma exacerbations was older than the other group (4.3±0.9 compared to 3.7±0.7 years old, p=0.01). Also, the length of stay (LOS) was shorter in the patients with HRV-induced asthma exacerbations compared to the patients with other virus-induced exacerbations (3.2±1.5 compared to 4.4±2.7 days, p=0.04). To conclude, HRV-C was the most popular agent among hospitalized virus-induced asthma exacerbations in Vietnamese preschoolers. Compared to hospitalized asthmatic patients infected by other viruses, patients with HRV infection were older and had shorter LOS.